THE DEATH OF HAJJ PILGRIMAGES DURING THE WAITING PERIOD AND ITS IMPACT ON THE INHERITANCE SYSTEM AT THE MINISTRY OF RELIGION'S OFFICE EAST KUTAI DISTRICT - Sofiansyah (Awang Long Law Review, 2023)
The heirs who receive the delegation of portion numbers of the Hajj congregation who died, do not reduce their share of inheritance and its impact on the inheritance system. This study aims to analyze the procedure for delegating the portion number of Hajj congregation who died during the waiting period at the Office of the Ministry of Religious Affairs of Kutim Regency, analyze the problems faced by the heirs in the delegation of the portion number of the Hajj congregation who, and analyze the determination of the heirs who receive the delegation of the portion number and its impact on the inheritance system taken by the family of the Hajj congregation who died during the waiting period. The type of research is empirical legal research. The approach in this research uses a normative sociological approach. Data were collected by observation, interview, and documentation. Data analysis in this research is qualitative with the Induction way of thinking. The results showed that the procedure for delegating portion numbers in accordance with the Kepdirjen Number 130 of 2020 about Implementation Guidelines for the delegation of portion numbers for hajj congregation who died or were permanently ill. The problem faced is the distance-time-cost. Determination of the heirs who receive the delegation of the portion number is carried out through discussion and it does not reduce their inheritance. So that it does not have an impact on the inheritance system in the family of the heir.